2018
DOI: 10.1017/s0950268818001978
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection in oral cancer patients in China: a case–control prospective study

Abstract: Over the recent years, potential associations between Toxoplasma gondii (T. gondii) infection and cancer risk have attracted a lot of attention. Nevertheless, the association between T. gondii infection and oral cancer remains relatively unexplored. We performed a case-control study of 861 oral cancer patients and 861 control subjects from eastern China with the aim to detect antibodies to T. gondii by enzyme-linked immunosorbent assay (ELISA) in these patients. The results showed that oral cancer patients (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…However, in immunocompromised patients, such as those with a tumor, T. gondii may cause a serious, life-threatening infection. Several studies demonstrate a latent relationship between toxoplasmosis and malignancy, including with brain and oral cancers [ 7 9 ]. In recent studies, patients with hematologic malignancies had higher seroprevalence of T. gondii antibodies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in immunocompromised patients, such as those with a tumor, T. gondii may cause a serious, life-threatening infection. Several studies demonstrate a latent relationship between toxoplasmosis and malignancy, including with brain and oral cancers [ 7 9 ]. In recent studies, patients with hematologic malignancies had higher seroprevalence of T. gondii antibodies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humans can develop toxoplasmosis when they ingest oocysts shed by cats or tissue cysts in other mammals [ 4 ]. Many factors are associated with toxoplasmosis in cancer patients, including contact with pigs or cats, consumption of raw or undercooked meat, and exposure to soil [ 9 , 10 , 13 ]. Moreover, histories of blood transfusion and chemotherapy are also risk factors for T .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the positive T. gondii antibodies increased with age in healthy children, but in young patients with malignancy, T. gondii is likely to occur [5, 15, 18]. This could be attributed to the fact that younger patients with malignancy may be immunocompromised and are inclined towards the T. gondii infection [5, 6]. However, the reasons that younger ML patients were susceptible to T. gondii infection have not been well explained, thereby necessitating further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the immunocompromised host, the cysts can infect various organs, such as the liver, spleen and nervous system, which, in turn, cause severe symptoms as well as death [3,4]. Currently, T. gondii infection in patients with malignancy is of great concerns, and thus, the correlations between T. gondii infection and malignancy have been evaluated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%